La regulación de los datos genéticos y las bases de datos de ADN - Guerrero Moreno, Álvaro Alfonso (2023)
Today the use of DNA is an essential way of conducting research within the scope of the administration of justice, and it is a test universally used and accepted in the biological research of parenthood (civil cases) and in criminal matters; furthermore, the use of DNA is very useful for the investigation of dead and missing persons. This article will discuss some of the problems that have risen in relation to advances in genetics and law. Some of these problems are creating a special category of genetic data, having a personal and delicate character; the existent regulation in genetic data at the international level, and also in the European Community and Spain; and the issue of the use of DNA profiling, more specifically of creating a single database of DNA data for criminal investigation.